In the court of the gentiles: narrative, exemplarity, and scriptural adaptation in the court-tales of Flavius Josephus - Edwards, David R. (Journal for the study of Judaism / Supplements, 2023)
"David Edwards explores how Josephus in Antiquities adapts the scriptural stories of Joseph and Esther in unexpected ways as models for accounts of more recent Jewish figures. Terming this practice "subversive adaptation," Edwards contextualizes it within Greco-Roman literary culture and employs the concept of "discourses of exemplarity" to show how Josephus used narratives about past figures to engage Roman elites in moral reflection and pragmatic decision-making. This book supplies analysis of frequently overlooked accounts as well as Josephus' broader literary strategies, and shows how ancient Jews appropriated imperial historiographical conventions and forms of discourse while countering Greco-Roman claims of cultural superiority"--